Jalas et al. Self-Building Courses of Solar Heat Collectors as Sources of Consumer Empowerment and Local Embedding of Sustain... - Jalas, Mikko; Kuusi, Helka; Heiskanen, Eva (Science & technology studies, 2014)
Self-building courses have been identified as a stimulus for user innovations, local embedding and diffusion of renewable energy technology. In this paper we explore the Finnish solar heat collector self-building courses. Our empirical material consists of field observations, interviews with teachers and a survey of participants since the early activities in late 1990s. Our findings show that course participants have started to follow energy discussions, collect information and actively advise others. Participants view themselves as increasing capable actors in renewable energy. They have also begun to engage in energy saving and renewable energy at home on a wide front. The fact that only 41% have installed their collector points to the importance of timing but also to the way in which self-building courses serve as a first step into renewable energy. Overall our results indicate that self-building courses offer possibilities for material engagement that has outcomes beyond the immediate objectives of the course.
Keywords: solar heat collectors, self-building, material engagement